Pengaruh Pendidikan, Pelatihan dan Komitmen Organisasi terhadap Kinerja Karyawan Universitas Muhammadiyah Jember - Salsabila, Azza Aulia; Izzudin, Ahmad; Nursaidah, Nursaidah (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research was conducted to determine the influence of education, training and organizational commitment on employee performance at Muhamadiyah University Jember (UNMUH Jember). This research uses a quantitative method with a purposive sampling method of 199 respondents, using an electronic survey distributed to employees at the Muhammadiyah University of Jember. The data analysis used is the multiple linear regression test, partial test (t test), and coefficient of determination test (R2). And the results of the analysis using SPSS version 25 show that the education variable has a significant effect on employee performance, while training and organizational commitment do not have a significant effect on employee performance. Keywords: Education, Employee Performance, Organizational Commitment, Training.